Peran DPR dalam Pengangkatan Duta Besar Setelah Amandemen UUD 1945 - Mariana; Ibrahim (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2021)
The research objectives were to determine the role and power of the DPR in the appointment of the Indonesian Ambassador after the amendments to the 1945 Constitution, and to regulate the procedures for the appointment of the Indonesian ambassador. The research method used is literature study with the study of the Constitution, laws and regulations. DPR Standing Orders, literatures, the news letter, papers and results of studies on the problems studied, and data analysis using descriptive methods, namely researching current facts and reporting what will happen. Where the appointment of ambassadors is no longer the perfect prerogative of the President. One of the rights held by the DPR is the right to give consideration in the appointment of ambassadors and the acceptance of ambassadors from friendly countries. The DPR then gives consideration to each candidate for ambassador proposed by the government. Then the DPR, through the leadership of the council, delegates this power to the commission, in this case the commission in charge of the matter in question. Commission I, as the apparatus of the DPR in charge of foreign relations, subsequently this commission determines the agenda for the meeting which summons candidate ambassadors to conduct discussions by holding a General Hearing Meeting.